Motivation of Workers on Microtask Crowdsourcing Platforms - Naderi, Babak (T-Labs Series in Telecommunication Services,, 2018)
This book studies the motivation of crowdworkers to find out how to attract more people and reach a higher quality of outcomes. The book first proposes a taxonomy for studying the motivation of crowdworkers including the potential influencing factors, different types of motivation, and possible consequences and outcomes related to the motivation. Next, the CWMS questionnaire, an instrument for measuring the underlying motivation of crowdworkers is developed. It considers different dimensions of motivation suggested by the Self-Determination Theory of motivation which is a well-established and empirically validated psychological theory used in various domains. This instrument can be used to study the effect of platform and user characteristics on the general motivation of crowdworkers. Later, the task-specific motivation of crowdworkers is studied in detail: Influencing factors are investigated, subjective methods for measuring them are evaluated, a model for predicting worker's decision on taking a task is proposed, the relative importance of different factors for two populations of crowdworkers is studied, and finally, a model for predicting the expected workload (as one of the major influencing factors) given the task design is proposed.